SCIENTIFIC ACTIVITIES OF SCIENTISTS WORKING ON PSYCHOLOGICAL THEORIES OF MEMORY - Makhkamova Mastura Bakhromjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The article provides information about the opinions of scientists and the theories they gave about the first psychological theories of memory. Based on this theory, the association -G. Concepts of connection between certain unique phenomena of the psyche developed by Ebbingauz, G. Müller, A. Pilseker and others are highlighted.